Management of Breast Milk Donor (Istirdla) in Institution of Lactashare Application and Facebook of Breastmilk Donor Based on Islamic Law - Fauziah, Faridatul; Muchlis, Fauziah Muchammad Fauzan; Putri, Imas (Riwayat: Educational Journal of History and Humanities, 2024)
This study is a qualitative study with a normative juridical approach, namely an approach that relies on laws and regulations as the main material to provide arguments for the hypotheses and perspectives that researchers present. The data used in this article are secondary data that researchers obtain from various credible sources, namely laws and regulations. The data used are analyzed using comparative legal interpretation techniques with the interpretation results below. According to its type, this research is normative legal research, namely doctrinal legal research, research that examines a set of theories or related written rules, or research like this which is also common in the world of research is called library research, namely research that emphasizes extracting sources. legal materials from the library.